The study of Upper Palaeolithic and Mesolithic in Portugal: a historiographic perspective - Bicho, Nuno (2018)
The scientific study of the Upper Palaeolithic, Epipaleolithic and Mesolithic hunter-gatherers in Portugal has its roots in the mid-19th century. The 2nd Geological Commission, created by a decree of the queen D. Maria II (1857), played a fundamental role in the study of this period and in the recognition of the first Palaeolithic and Mesolithic deposits. This Institution, with brilliant elements such as Pereira da Costa, Carlos Ribeiro, Nery Delgado, have allowed the implementation of Prehistory and Archeological studies and brought worldwide recognition to the deposits such as the caves of the Casa da Moura and Furninha or the Muge Mesolithic shellmiddens. With the 20th century, the work of scientific research on hunter-gatherers was centered mainly on the Universities of Porto and Lisbon, the National Museum of Archeology and the Geological Service, developing work predominantly on the Atlantic coast and in the valleys of the great rivers Portuguese. The research in Africa with Mendes Corrêa and Santos Júnior through the Anthropological Missions of Estado Novo in the 1930’s must also be mentioned. In the last quarter of the century. Upper Palaeolithic and Mesolithic research was a major development not only in the interest of some, unfortunately scarce, Portuguese university students, but also by foreigner experts. Since the last decade of the millennium, the number of doctorates and Portuguese experts in these periods has greatly grown with the implementation of university studies in the Universities of Lisbon and Algarve, from which there has been a continued development of the study of the Upper Palaeolithic, Epipaleolithic, and Mesolithic in Portugal.